Age of Crime Onset and Psychopathic Traits in Female Juvenile Delinquents - Pechorro, Pedro (2013)
The aim of this study was to analyze the role of psychopathic traits in the age of crime onset of female juvenile delinquents. Using a sample of 132 young females from the Juvenile Detention Centers of the Portuguese Ministry of Justice and from schools in the Lisbon region, a group of early crime onset (n = 44), a group of late crime onset (n = 44), and a nondelinquent school group (n = 44) were formed. Results showed that early crime onset participants score higher on psychopathy measures, self-reported delinquency, and crime seriousness than late crime onset participants and school participants. Psychopathic-traits scores were significantly associated with age of crime onset, age at first trouble with the law, and frequency and seriousness of crime.